DIAGNOSTIC ACCURACY OF 99 MTC LABELLED UBIQUICIDIN (29-41) SPECT/CT FOR DIAGNOSIS OF OSTEOMYELITIS IN DIABETIC FOOT - Atif, Muhammad; Hussain, Fida; Dar, Zaigham Salim; Khatoon, Jameela; Ajmal, Saadia; Adil, Muhammad (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine diagnostic accuracy of 99mTc labelled Ubiquicidin (29-41) SPECT/CT for detection of osteomyelitis in diabetic foot patients by taking bone biopsy as gold standard.Study Design: Cross-sectional validation study.Place and Duration of Study: Nuclear Medical Centre, Armed Forces Institute of Pathology, from Apr 2017 to Mar 2018.Methodology: Study assessed 122 patients of both genders, aged between 30-80 years (mean age=55.3 years), presenting with diabetic foot ulcers having suspicion of osteomyelitis, by 99mTc-Ubiquicidin (29-41) SPECT/CT followed by bone biopsy (histopathology and culture) taken as gold standard.Results: Among 122 patients [94 male (77%) and 28 female (23%)], osteomyelitis was histopathologically confirmed in 113 patients. 107 out of these patients were positive for osteomyelitis on 99mTc-UBI (29-41) SPECT/CT (true positives) while 6 were false negative. Out of 9 patients declared negative for osteomyelitis on histopathology and culture, 8 were negative on 99mTc-UBI (29-41) SPECT/CT as well (true negative) while only 1 case came out to be positive (false positive). Thus, the 99mTc-UBI (29-41) scan showed 94.6% sensitivity, 88.89% specificity, 99% positive predictive value, 57% negative predictive value with overall 94.2% diagnostic accuracy.Conclusion: 99mTc labelled Ubiquicidin (29-41) SPECT/CT scan can precisely localize infective focus, in diabetic foot osteomyelitis, with simultaneous discrimination between bone and soft tissues.